Sebuah Alternatif: Better Life Index sebagai Ukuran Pembangunan Multidimensi di Indonesia - Pratomo, Dody; Sumargo, Bagus (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
The purpose of this study is to get value-BLI Better Life Index as a measure of multidimensional development in Indonesia, and to analyze the relationship between BLI with the human development index HDI, regional development index IPR, and economic growth. BLI formation method through three stages: normalization, weighting, and aggregation. The results show that Indonesia’s BLI is in the lower-middle class. Province of Jakarta, East Kalimantan, North Sulawesi, Riau and South Sumatra with the highest value of BLI. BLI size has a positive and significant correlation with IPM and IPR compiled by the BPS-Statistics Indonesia. However, BLI was a negative and significant correlation with economic growth.